A Pilot Randomized Controlled Trial Comparing Mindfulness Meditation, Cognitive Therapy, and Mindfulness-Based Cognitive Therapy for Chronic Low Back Pain - Day, Melissa A; Ward, L Charles; Ehde, Dawn M; Thorn, Beverly E; Burns, John; Barnier, Amanda; Mattingley, Jason B; Jensen, Mark P (Pain medicine (Malden, Mass.), 2019)
Abstract Objective This pilot trial compared the feasibility, tolerability, acceptability, and effects of group-delivered mindfulness meditation (MM), cognitive therapy (CT), and mindfulness-based cognitive therapy (MBCT) for chronic low back pain (CLBP). Setting University of Queensland Psychology Clinic. Subjects Participants were N = 69 (intent-to-treat [ITT] sample) adults with CLBP. Design A pilot, assessor-blinded randomized controlled trial. Methods Participants were randomized to treatments. The primary outcome was pain interference; secondary outcomes were pain intensity, physical function, depression, and opioid medication use. The primary study end point was post-treatment; maintenance of gains was evaluated at three- and six-month follow-up. Results Ratings of acceptability, and ratios of dropout and attendance showed that MBCT was acceptable, feasible, and well tolerated, with similar results found across conditions. For the ITT sample, large improvements in post-treatment scores for pain interference, pain intensity, physical function, and depression were found (P < 0.001), with no significant between-group differences. Analysis of the follow-up data (N = 43), however, revealed that MBCT participants improved significantly more than MM participants on pain interference, physical function, and depression. The CT group improved more than MM in physical function. The MBCT and CT groups did not differ significantly on any measures. Conclusions This is the first study to examine MBCT for CLBP management. The findings show that MBCT is a feasible, tolerable, acceptable, and potentially efficacious treatment option for CLBP. Further, MBCT, and possibly CT, could have sustained benefits that exceed MM on some important CLBP outcomes. A future definitive randomized controlled trial is needed to evaluate these treatments and their differences.